USE OF HUMAN CORD BLOOD AS DNA EVIDENCE IN PATERNITY DISPUTES: A CASE STUDY - Mohapatra, BK; Dagar, Seema; Aggarwal, Kangana; Behera, Chittaranjan (Journal of Forensic Medicine and Toxicology, 2025)
This study explores the use of umbilical cord blood for DNA profiling in paternity disputes, offering a practical alternative to traditional fetal or neonatal blood sampling with higher yield and no maternal contamination.